Polymorphism of the FTO Gene Influences Body Weight in Children with Type 1 Diabetes without Severe Obesity - Łuczyński, Włodzimierz (Hindawi Publishing Corporation, 2014)
The objective was to compare the impact of clinical and genetic factors on body mass index (BMI) in children with type 1 diabetes (T1DM) without severe obesity. A total of 1,119 children with T1DM (aged 4–18 years) were qualified to take part in the study. All children were genotyped for variants of FTO, MC4R, INSIG2, FASN, NPC1, PTER, SIRT1, MAF, IRT1, and CD36. Results. Variants of FTO showed significant association with BMI-SDS in the T1DM group. The main factors influencing BMI-SDS in children with T1DM included female gender (P = 0.0003), poor metabolic control (P = 0.0001), and carriage of the A allele of the FTO rs9939609 gene (P = 0.02). Conclusion. Our research indicates, when assessing, the risk of overweight and obesity carriage of the A allele in the rs9939609 site of the FTO gene adds to that of female gender and poor metabolic control. This trial is registered with ClinicalTrials.gov (NCT01279161).